The role of women as peace builders: the model of Russia - Akhmetova, Elmira (2016)
This paper discusses the status of Muslim women in Russia from historical, social, cultural and political perspectives. It discusses the achievements of Muslim women in creating peaceful and amicable environment in Russia and their struggles against Islamophobia and negative stereotypes.